2008
DOI: 10.1007/s10164-007-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Nest defence in the meadow pipit Anthus pratensis: the influence of renesting potential

Abstract: The reproductive value hypothesis predicts that the level of nest defence is determined by the expected chance of offspring to survive until reproduction, and by the reproductive potential of the parents. Rates of survival from one breeding season to the next are low in small passerines, and their residual reproductive potential strongly declines as the current breeding season terminates. Therefore, we can expect that parents which have only one breeding attempt per season should defend their nests more intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The risk to parents when defending their brood is known to increase with decreasing distance to the predator and with increasing intensity of display (defensive) behaviour (Montgomerie & Weatherhead 1988; Brunton 1990; Lima & Dill 1990; King 1999, Pavel & Bureš 2001, 2008). Socially monogamous great reed warbler males defended their nests more intensively than socially polygynous males defending the nest of their primary female.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk to parents when defending their brood is known to increase with decreasing distance to the predator and with increasing intensity of display (defensive) behaviour (Montgomerie & Weatherhead 1988; Brunton 1990; Lima & Dill 1990; King 1999, Pavel & Bureš 2001, 2008). Socially monogamous great reed warbler males defended their nests more intensively than socially polygynous males defending the nest of their primary female.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that nest defence increases with the number and age of offspring, parental condition and with the decline of renesting potential (reviewed by Montgomerie & Weatherhead 1988; Pavel & Bureš 2001, 2008). At the time of each experiment, we therefore recorded the number of nestlings and the date during the breeding season.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual near the end of life should not pass up an opportunity to reproduce, even if fighting is required, if it is unlikely to find another reproductive opportunity. In a similar manner, when the probability of survival is low, individuals of diverse taxa are known to expose themselves to greater risks of predation to prepare to breed (Lafaille et al 2010;Kuriwada et al 2011;Schwanz et al 2012) or to greater risks in defending young (Pavel and Bures 2008;Steinhart et al 2008), consistent with RRV models.…”
Section: Two Models Of Reproductive Effortmentioning
confidence: 72%
“…As nesting attempt progresses the value of the nest increases, and parents tend to defend their nests more intensely and tolerate a higher predation risk (Montgomerie and Weatherhead 1988;Anderson et al 1980;Brunton 1990;Rytkönen et al 1990;Redondo 1989;Albrecht and Klvaña 2004). Moreover, as the breeding season progresses, the opportunity for renesting decreases, and the need to save the current breeding attempt increases too, which constrains parents to take higher predation risks and to tolerate closer approaches of predators (Trivers 1972;Barash 1975;Montgomerie and Weatherhead 1988;Redondo 1989;Pavel and Bureš 2008). However, little is known about the possible role of the interaction between the two factors in shaping bird nest-defence behaviours.…”
Section: Introductionmentioning
confidence: 96%